EKSEKUSI DALAM PEMBAGIAN HARTA BERSAMA DI PENGADILAN AGAMA - Masykuroh, Yuvi Wiyos Rini (Universitas Islam Negeri Raden Intan Lampung, 2014)
The main steps in the process to be followed in courtif the parties in court-ordered mediation do not reachan agreement, they can proceed with their case incourt. They proceed to trial on the court case and letthe judge resolve the matter. When the judgecompleted his case based on the judge's decision anddetermination. Judge's decision is binding on thedisputing parties, both parties to carry out thedecision. Regarding the division of marital propertythat had been decided upon in the Religious Court isthe case in the decision comdemnator. This decisioncontains the execution, If one party or the otherdoesn't fulfil the judge’s decision, based on the ofother side, court decisions apply to the Chief court toenforce the execution.